PENGARUH PEMBELAJARAN DARING (E-LEARNING) TERHADAP PRESTASI BELAJAR MAHASISWA PENDIDIKAN MASYARAKAT PADA SEMESTER GANJIL 2020/2021 FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Ersa Fitrila Tania; Wilson Wilson; Jaspar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effect of online learning (e-learning) on the learning achievement of Community Education Students, Faculty of Teacher Training and Education, University of Riau. The formulation of the problem in this study is whether there is an effect of online learning (e-learning) on the learning achievement of Community Education Students. This study consists of 2 online learning variables (e-learning) (X) and learning achievement (Y), where the online learning variable (e-learning) has 4 indicators and learning achievement variables use a measurement system using the learning achievement index listed in the KHS (Study Result Card) students. The population in this paper is the 2018 & 2019 Community Education Students with 95 students. The sampling technique with stratified random sampling used was proportionate stratified random sampling with a total of 20 trial samples and 49 research samples. The data collection technique in this study was a questionnaire technique through google form, which amounted to 41 statements for the online learning (E-learning) variable. After the questionnaire was tested, there were 5 invalid statements on the e-learning variable, and the researcher discarded the invalid statements. Based on descriptive analysis based on variables, the learning achievement level is obtained with a mean of 3.60 which is in a very good interpretation, based on a descriptive analysis of variables, it is obtained online learning (e-learning) with a mean of 3.44 which is in a high interpretation. A significant effect was obtained between the variables of Online Learning (E-learning) (X) on the learning achievement (Y) of the students of Community Education, Faculty of Teacher Training and Education, Riau University, which had a large effect of 10.5% with a low interpretation. Because there are still 89.5% determined by other factors that are not part of this writing.Key Words: Online Learning (E-Learning), Learning Achievement,Community Education Students